Gandrung Dance Performance as a Media for Hindu Religious Education at Pura Dalem Majapahit - Tri Utami, Ni Nyoman Dian; Sudarsana, I Ketut (EduLine: Journal of Education and Learning Innovation, 2022)
Education for human life is an absolute need to be fulfilled and plays a very important role in the preservation of cultural heritage. Art is a cultural heritage. In Pemecutan Kelod Village, Denpasar City, there is a sacred art, namely the Gandrung dance which is staged during the piodalan series at the Dalem Majapahit Temple. Only boys can dance. The problems discussed are 1) How is the Gandrung Dance Performance Procession as a Media for Hindu Religious Education at Pura Dalem Majapahit Br. Munang Maning Pemecutan Kelod Village, Denpasar City? 2) What are the factors behind the Gandrung Dance Performance as a Hindu Religious Education Media at Pura Dalem Majapahit, Br. Munang Maning Pemecutan Kelod Village, Denpasar City? 3) What educational values ​​are contained in the Gandrung dance performance as a Hindu Religious Education Media at Pura Dalem Majapahit Br. Munang Maning Pemecutan Kelod Village, Denpasar City?. This research is classified as qualitative research. Data were obtained by using data collection methods, observations, interviews, literature studies and documentation. The data that has been collected is then analyzed using descriptive methods at the stages of reduction, data presentation, and drawing conclusions. The results of this study indicate: 1) Gandrung dance performances at Pura Dalem Majapahit, namely: patching gelungan gandrung, wearing make-up, pawintenan, ngaturang bhakti, wearing gelungan, mecaru, mesolah and pemuput. 2) The factors behind the performance of the Gandrung dance can be seen from the function of adaptation, goal achievement, integration, and latency. 3) Hindu religious education values ​​contained in the Gandrung Dance Performance: (a) skill values, (b) ethical values, (c) aesthetic values, (d) cultural preservation values, (e) love values.